PROSEDUR KLAIM BPJS KESEHATAN PASIEN RAWAT JALAN GUNA MENUNJANG PELAYANAN KESEHATAN DI RUMAH SAKIT - Maimun, Nur; Natassa, Jihan; Maria Ulfa, Henny; Salsabillah (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
The Social Security Administering Body (BPJS) is a program as a follow-up to the National Health Insurance (JKN). The BPJS claim process requires files that are used as a condition for accepting the claim. The files will be processed by Casemix staff after the patient has finished receiving services. Bina Kasih Hospital indicated that there were incomplete files for hospital billing costs and filling in the patient's way of going home when entering the identity of the outpatient BPJS Health patient. If the proof of service is not completed and supporting sheets such as hospital billing costs are not yet available, then the case-mix officer will not be able to process the outpatient BPJS Health claim. This research aims to determine the BPJS Health claim procedure for outpatients to support health services. This type of research is a qualitative descriptive study with 2 informants (1 Casemix head, and 1 Casemix officer). The research location was at Bina Kasih Hospital Pekanbaru in June – August 2023 using observation guidelines and interview guidelines. The results of the research are that the BPJS will only verify outpatient files if all the files are complete, the procedure flow for submitting an outpatient BPJS Health claim at Bina Kasih Hospital in writing does not yet exist, the BPJS Health Claim SPO for outpatients already exists in writing, but it is still there is no separation between outpatient and inpatient SPO. It is hoped that the BPJS Health files for outpatients must be complete before a claim is made and the SPO for BPJS Health claims files at Bina Kasih Hospital is made separately between the SPO for outpatient claims files and the SPO for inpatient claims files